1985
DOI: 10.2466/pms.1985.60.2.551
|View full text |Cite
|
Sign up to set email alerts
|

Physical Training and Personality Factors as Predictors of Marathon Time and Training Injury

Abstract: On the basis of surveys completed by 105 male participants in a popular marathon, a multiple regression analysis was conducted to identify the variables contributing significantly to the prediction of final time. Overall prediction was successful, with R = .896, and training pace was the most important factor in the equation, speedier workouts being associated with faster marathon times. Final time was also related positively to best 10-km race time in the previous 12 mo. and repression-sensitization (faster r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 15 publications
3
26
0
1
Order By: Relevance
“…On one hand, neither trait nor state anxiety exert a sizeable effect on performance in both laboratory situations and under the practice condition as well. This is in full accordance with the results of previous studies with runners (Reilly, 1977;Sanderson & Reilly, 1983;McKelvie et al, 1985). On the other hand, it is in line with theoretical expectations to find, at least for one subgroup, an inverted-U relationship between anxiety and the running performance in the competition.…”
Section: Eflects Of Anxiety On Performancesupporting
confidence: 92%
See 1 more Smart Citation
“…On one hand, neither trait nor state anxiety exert a sizeable effect on performance in both laboratory situations and under the practice condition as well. This is in full accordance with the results of previous studies with runners (Reilly, 1977;Sanderson & Reilly, 1983;McKelvie et al, 1985). On the other hand, it is in line with theoretical expectations to find, at least for one subgroup, an inverted-U relationship between anxiety and the running performance in the competition.…”
Section: Eflects Of Anxiety On Performancesupporting
confidence: 92%
“…Reilly, 1977;Sanderson 8z Reilly, 1983). In accordance with these results, McKelvie, Valliant, and Asu (1985) also did not find linear or nonlinear effects of anxiety on marathon performance. To get a clearer impression, the present study was designed to contain-in addition to the field setting (practice and competition)-a laboratory phase, in which an easier manipulation of the treatment as well as a better standardization and control of the situation can be expected.…”
supporting
confidence: 86%
“…We must assume that duration of training was of higher importance than training speed. Different studies of runners described that volume of training was important for performance as well [17, 19, 20, 31] . McKelvie et al described that training pace was important for runners and speedier workouts were associated with faster marathon times [31] .…”
Section: Discussionmentioning
confidence: 99%
“…McKelvie, Valliant, and Asu (1985) failed to find a relation between either association or dissociation and injury. Two other studies, one with masters track and field athletes (Ungerleider, Golding, Porter, & Foster, 1989) and another with swimmers (Bond, Miller, & Chrisfield, 1988) even suggested that association may be positively re-COGNITIONS AND INJURY AMONG RUNNERS 283 lated to injury.…”
Section: Masters and Oglesmentioning
confidence: 95%